Knowledge of Thalassemia Caregivers Attending the Thalassemia and Congenital Blood Disorder Center, Sulaimaniyah, Iraq - Ahmed, Chiman Jamal; Aziz, Karim Fatah; Amin, Muhamad Rashid (Sulaimani Journal for Pure and Applied Sciences, 2024)
Background: Thalassemia is the leading hemoglobinopathy and a common public health problem in Iraq. About 7% of the Iraqi people are carriers of this genetic disorder. Aim: To assess parents' accurate knowledge about thalassemia disease in Sulaimaniyah, Iraq. Subjects and Methods: This descriptive-analytic study was conducted on 304 caregivers of thalassemia patients at the Thalassemia and Congenital Blood Disorder Center, Sulaimaniyah, Iraq, from February to July 2022—a validated questionnaire collected caregivers' characteristics and knowledge of the thalassemia condition. Results: Regarding the thalassemia patients’ caregivers’ sociodemographic data, most of them were aged 36-49 years old (67.1%), females (59.2%), mothers (61.8%), housewives (59.2%), lacked formal education (48.7%), had not enough income (57.9%), and from urban area (78.9%), without chronic disease (76.3%). Also, most caregivers were not undergoing premarital testing (81.6%), expressed readiness for antenatal testing (63.2%), had a poor level of general knowledge about thalassemia (73.7%), and agreed to abort their fetus if they knew about the condition during pregnancy (59.2%). Regarding thalassemia caregivers’ level of knowledge, most caregivers (73.7%) had poor general knowledge, 44.7% had good prevention knowledge, 65.8% had good treatment knowledge, 61.8% had good perception, and 35.5% had a fair overall understanding. There was a significant difference between knowledge level and gender, occupation, education, relation, and residency (p=0.000). Regarding antenatal tests, caregivers who had not performed these tests had a significantly lower mean knowledge level than those who had (p=0.000). Conclusions: There needs to be more knowledge among patients' caregivers regarding thalassemia. Thus, intensive courses and training should be given to them to improve their understanding.
Keywords: Caregiver; knowledge; thalassemia; analytical study